Pengaruh Konseling Kesehatan terhadap Minat Penundaan Kehamilan Beresiko pada Pasangan Usia Subur (PUS) - A. Hiola, Fidyawati Aprianti; Husna Ali, Rizky Nikmathul; Sondakh, Levana; Katili, Tressan Eka Putri; Mulyaningsih, Sri (STIKes Hamzar, 2025)
Pregnancy at age < 20 years has a high risk to the health of the mother and baby. Low knowledge and awareness of fertile couples (PUS) often causes a lack of interest in postponing pregnancy. Health counseling is seen as one of the effective interventions to increase interest in postponing risky pregnancies. Aims To determine the effect of health counseling on the interest in postponing risky pregnancies in PUS <20 years. This study used a pre-experimental design with the One Group Pretest-Posttest Design approach. The sample consisted of 22 PUS respondents aged <20 years selected through purposive sampling techniques. The research instruments were Flip Sheets and questionnaires. Data analysis used the Wilcoxon test .Results: There was an increase in the interest score of postponing pregnancy after being given health counseling. The results of the statistical test showed a significance value of p <0.05 , which means that there is a significant influence between health counseling and the interest of PUS <20 years in postponing pregnancy. Conclusion: Health counseling is effective in increasing interest in postponing risky pregnancies in fertile couples under 20 years of age. This intervention can be used as a promotive-preventive strategy in adolescent reproductive health programs..